Normstabilisierung und Schuldvorwurf - Simmler, Monika (sui generis, 2018)
This work examines the nature of criminal responsibility, and thereby the very heart of criminal law theory. The analysis exposes the relevance of criminal law and punishment for the stabilization of norms within society. This allows to determine the function of placing blame and of the principle of culpability. Thus, this thesis offers in-depth insights into the mechanism and elements of the attribution of individual responsibility. The main finding is that only culpability and the consideration of its elements, which are defined in this work, are capable of functionally determining punishment (i.e., in accordance with the necessity of punishment for the stabilization of norms).